Pengaruh Work Life Balance Terhadap Kinerja Pegawai pada Kantor Dinas Tenaga Kerja Kota Samarinda (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study was motivated by the importance of work-life balance in supporting employee performance, particularly in government bureaucratic environments such as the Samarinda City Manpower Office. The purpose of this study was to determine the effect of work-life balance on employee performance. This study used a quantitative approach with a survey method by distributing questionnaires to all 64 employees. The data analysis technique used is simple linear regression with the assistance of SPSS software version 25. The results of the study indicate that Work-Life Balance has a positive and significant influence on employee performance, with a significance value of 0.024. However, the coefficient of determination was only 0.080, indicating that the influence of Work-Life Balance on performance explains only 8% of the variation in employee performance, while the remainder is influenced by other factors. This finding implies that while Work-Life Balance is important, government agencies need to develop more comprehensive performance management strategies by considering other factors such as motivation, organizational culture, and reward systems to optimize employee performance.